Distinct OPDA Biosynthesis Pathways in the Liverwort Marchantia polymorpha and the Moss Physcomitrium patens - Yuho Nishizato; Yuki Hata; Takuya Kaji; Mai Morikawa; Junko Kyozuka; Minoru Ueda (Journal of Plant Growth Regulation, 2026)

Tree retention for conserving saproxylic beetles in harvested conifer plantations - Satoshi Yamanaka; Akira Ueda; Naoyuki Furuya; Takuya Kobayashi; Hideaki Goto; Kenichi Ozaki (Forest Ecology and Management, 2025)

Seasonal timing of ecosystem linkage mediates life‐history variation in a salmonid fish population - Rui Ueda; Minoru Kanaiwa; Akira Terui; Gaku Takimoto; Takuya Sato (Ecology, 2025)
Life‐history variation can contribute to the long‐term persistence of populations; however, it remains unclear which environmental factors drive life‐history variation within a population. Seasonally recurring resource subsidies are common in nature and may influence variations in recipient consumers' life‐history traits. In this study, we experimentally demonstrated that terrestrial invertebrate subsidies occurring early in the growing season facilitated consumer individuals to adopt fast growth. In contrast, fewer consumer individuals adopted fast growth when subsidies occurred late in the growing season. Consumer individuals that adopted fast growth matured early at age 1, suggesting that the observed variation in life history emerged along with a fast–slow life‐history continuum. The estimated survival probability was lower in consumer individuals from the faster growth cluster in the no‐supply treatment (control), suggesting a growth–survival trade‐off. However, the growth–survival trade‐off became unclear in the early‐supply treatment and even reversed in the late‐supply treatment. As a result, the frequency of consumer individuals maturing at age 1 was higher in the early‐supply treatment than in the late‐supply treatment and no‐supply treatment, implying a higher short‐term population growth with the early subsidies. Our findings highlight that seasonal ecosystem linkages through resource subsidies help us understand how life‐history variation can be maintained within a population at the landscape scale.

SlCYP94B18 and SlCYP94B19 monooxygenases for the catabolic turnover of jasmonates in tomato leaves - Rina Saito; Mai Morikawa; Toshiya Muto; Sayaka Saito; Takuya Kaji; Minoru Ueda (Phytochemistry, 2024)

Distribution and Effects of Selenoneine by Ingestion of Extract from Mackerel Processing Residue in Mice - Takuya Seko; Yoko Sato; Michiko Kuniyoshi; Yuko Murata; Kenji Ishihara; Yumiko Yamashita; Sanjuro Fujiwara; Tomohiro Ueda; Michiaki Yamashita (Marine Biotechnology, 2023)

Difficulty in sex identification of two local populations of red-spotted masu salmon using two salmonid male-specific molecular markers - Rui Ueda; Hirohiko Takeshima; Takuya Sato (Ichthyological Research, 2022)

Genetic diversification of the Kanehira bitterling Acheilognathus rhombeus inferred from mitochondrial DNA , with comments on the phylogenetic relationship with its sister species Acheilognathus barbatulus - Takuya Miyake; Jun Nakajima; Keitaro Umemura; Norio Onikura; Takayoshi Ueda; Carl Smith; Kouichi Kawamura (Journal of Fish Biology, 2021)
The Kanehira bitterling, Acheilognathus rhombeus , is a freshwater fish, discontinuously distributed in western Japan and the Korean Peninsula. Unusually among bitterling it is an autumn‐spawning species and shows developmental diapause. Consequently, the characterization of its evolutionary history is significant not only in the context of the fish assemblage of East Asia, but also for understanding life‐history evolution. This study aimed to investigate the phylogeography of A. rhombeus and its sister species Acheilognathus barbatulus , distributed in China, using a mitochondrial analysis of the ND1 gene from 311 samples collected from 50 localities in Japan and continental Asia. Phylogenetic analysis revealed that A. barbatulus is included in A. rhombeus and genetically closer to Japanese A. rhombeus than to Korean A. rhombeus . Divergence of Korean A. rhombeus and A. barbatulus from Japanese A. rhombeus was estimated to be from the late Pliocene (3.44 Mya) and the early Pleistocene (1.98 Mya), respectively. Each event closely coincided with the time of the Japan Sea opening. Japanese A. rhombeus comprised seven lineages: three in Honshu and four in Kyushu. One lineage in central Kyushu was genetically closer to the Honshu lineages than to other lineages in northern Kyushu. Divergence of Japanese lineages was estimated to be from the early to middle Pleistocene (0.55–0.93 Mya), during a period of geological and paleoclimatic change, including volcanic activity. Population expansion in the late Pleistocene ( A. rhombeus / A. barbatulus was likely to have repeatedly colonized Japan from the continent through land bridges in the late Pliocene and the early Pleistocene. However, the close genetic relationship between Japanese A. rhombeus and A. barbatulus suggests another possibility, with the second colonization occurring in reverse, from Japan to China. The small genetic distance between them indicates that the colonization occurred later than colonization events of other freshwater fishes, including other bitterling species.

Anadromous red‐spotted masu salmon ( Oncorhynchus masou ishikawae ), a southernmost sea‐migration form of salmonid, displays low variation in both age at seaward migration and sea age - Shohei Noda; Rui Ueda; Tatsuya Tanaka; Kotaro Shirai; Daisuke Kishi; Takuya Sato (Journal of Fish Biology, 2021)
We examined variations in age at seaward migration and sea age for the anadromous form of red‐spotted masu salmon ( Oncorhynchus masou ishikawae ) in two Japanese rivers. The anadromous form of red‐spotted masu salmon expressed only two sea migration patterns in the two rivers: (a) the majority of the salmon (95%, n = 81) were of age‐0, and age‐1 migrants were rare ( n = 4); and (b) all the salmon examined ( n = 22) made a return migration within a year, with 23% of the salmon exhibiting potamodromy in the river. Owing to low variation in their sea migratory patterns, the anadromous form of red‐spotted masu salmon is likely vulnerable to environmental fluctuations.

Tumorigenesis in cells derived from induced pluripotent stem cells - Makoto Nishimori; Hiromasa Yakushiji; Michihiro Mori; Tomoyuki Miyamoto; Takahiro Yaguchi; Setsuyo Ohno; Yasuyuki Miyake; Takuya Sakaguchi; Masatsugu Ueda; Eiji Ohno (Human Cell, 2014)

Isolation of side population cells from endometrial cancer cells using a violet laser diode - Satoshi Tomiyasu; Tomoyuki Miyamoto; Michihiro Mori; Takahiro Yaguchi; Hiromasa Yakushiji; Setsuyo Ohno; Yasuyuki Miyake; Takuya Sakaguchi; Masatsugu Ueda; Eiji Ohno (Human Cell, 2014)

Effects of N-[N-(3, 5-difluorophenacetyl-l-alanyl)]-S-phenylglycine t-butyl ester (DAPT) on cell proliferation and apoptosis in Ishikawa endometrial cancer cells - Michihiro Mori; Tomoyuki Miyamoto; Hiromasa Yakushiji; Setsuyo Ohno; Yasuyuki Miyake; Takuya Sakaguchi; Manabu Hattori; Atsushi Hongo; Akihiko Nakaizumi; Masatsugu Ueda; Eiji Ohno (Human Cell, 2012)

A deletion in a cis element of Foxe3 causes cataracts and microphthalmia in rct mice - Kenta Wada; Yukiko Y. Maeda; Kei Watanabe; Tatsuya Oshio; Takuya Ueda; Gou Takahashi; Michinari Yokohama; Junichi Saito; Yuta Seki; Sumiyo Takahama; Rie Ishii; Hiroshi Shitara; et al. (Mammalian Genome, 2011)

The Distribution of Several Elements in Cat Urine and the Relation Between the Content of Elements and Urolithiasis - Mariko Mochizuki; Misato Morikawa; Takuya Yogo; Kimiyo Urano; Katsumi Ishioka; Minoru Kishi; Ryo Hondo; Fukiko Ueda; Toshinori Sako; Fujiro Sakurai; Norio Yumoto; Masahiro Tagawa (Biological Trace Element Research, 2011)

Poly-l-Arginine Enhances Paracellular Permeability via Serine/Threonine Phosphorylation of ZO-1 and Tyrosine Dephosphorylation of Occludin in Rabbit Nasal Epithelium - Kazuo Ohtake; Takuya Maeno; Hideo Ueda; Masahiko Ogihara; Hideshi Natsume; Yasunori Morimoto (Pharmaceutical Research, 2003)

Poly-L-Arginine Predominantly Increases the Paracellular Permeability of Hydrophilic Macromolecules Across Rabbit Nasal Epithelium in Vitro - Kazuo Ohtake; Takuya Maeno; Hideo Ueda; Hideshi Natsume; Yasunori Morimoto (Pharmaceutical Research, 2003)

The Cephalopod Loligo bleekeri Mitochondrial Genome: Multiplied Noncoding Regions and Transposition of tRNA Genes - Kozo Tomita; Shin-ichi Yokobori; Tairo Oshima; Takuya Ueda (Journal of Molecular Evolution, 2002)